The Overview of Ureteral Colic in Ureterolithiasis Patients Based on the Location of Stones Observed on Urographic CT-scan - Faris Taufiqurrahman; Chairunnisa; Hanina (Journal of Medical Studies, 2024)
ABSTRACT Background: Ureterolithiasis is a crystal concretion formed within the ureter that can lead to obstruction. Ureteral colic is one of the most common clinical manifestations with different characteristics depending on the location of the stone in the ureter. This research aims to determine the overview of ureteral colic in ureterolithiasis patients based on the location of stones that appeared on the urographic CT-Scan examination at RSUD Raden Mattaher Jambi. Methods: This research uses a qualitative study with a descriptive observational design, with 43 samples from the medical record data of ureterolithiasis patients in RSUD Raden Mattaher Jambi for January-December 2022. Results: The most incidence was male (69.8%) with age 41-60 years (44.2%). Ureteral colic predominates on the right side (53.5%), with the most radiating to the umbilical (44.2%). The most location was in the proximal ureter (44.2%), with hounsfield units <1000 HU (53.5%), and stone sizes were 5-10 mm and >10 mm (41.9%). Conclusion: Based on this research, the overview of ureteral colic in ureterolithiasis patients at RSUD Raden Mattaher Jambi was more common on the right side with the colic radiating to the umbilicus and the location stones in the proximal ureter. Keywords: ureterolithiasis; CT-scan urography; colic